DEMOCRATIC PEACE IN RELATION TO REGIONAL PEACE AND STABILITY IN THE WESTERN BALKANS - Popadić, Uroš (National interest, 2025)
The paper aims to apply the theory of democratic peace to the context of regional  peace and security in the Western Balkans, using both its internal external components. Due to the importance of regional democratisation for regional positive peace, as the theory would suggest, the recent democratic backsliding could negatively affect it. We provide a testing and adaptation of the famous theory and its recent adaptations and emerging corollaries, and produce a comparative regional empirical analysis to do so. After an overview of the democratic situation, and an analysis of regional relations, in the context of regional EU accession and the nominal role of the EU as a regional stabiliser or democratiser, we examine the implications for the region based on the theoretical insight and expectations. We found that there is a link between internal democratic practice and regional stability, as internal democratic issues led to deterioration of bilateral and multilateral cooperation, as well as to a slowing down of the EU accession process which is meant to contribute to peace in the region. We put forward the proposal that regional peace depends in many ways upon the continuation of democratisation in each regional state, which would contribute to an overall regional pacification even without direct external effort to that end. The results indicate that democratic backsliding would have a negative effect on regional peace and security, and vice versa, putting a normative emphasis on the continuation of regional democratisation.
Keywords: Western Balkans; Regional Stability; Peace and security; Democratisation; Democratic Peace Theory